Laboratory Testing for von Willebrand’s Disease: An Assessment of Current Diagnostic Practice and Efficacy by Means of a Multi-laboratory Survey - the RCPA Quality Assurance Program (QAP) in Haematology Haemostasis Scientific Advisory Panel; Favaloro, Emmanuel J.; on behalf of; Smith, Julian; Petinos, Penny; Hertzberg, Mark; Koutts, Jerry (Thrombosis and Haemostasis, 1999)
We report an evaluation of current laboratory practice for the diagnosis of von Willebrand’s disease (VWD) by means of a multilaboratory survey. This assessment was undertaken with the RCPA Quality Assurance Program (QAP) in Haematology, which covers a wide geographic area encompassing Australia, New Zealand and Asia. A total of 25 laboratories actively involved in testing for VWD were selected to participate in a sample testing assessment exercise. Samples comprised 10 plasmas: (i) a normal plasma pool (in duplicate), (ii) this pool diluted to 50% (in duplicate), (iii) a normal individual (×1), (iv) severe Type 1 VWD (×1), (v) Type 2B VWD (×2 unrelated donors), (vi) Type 3 VWD (×1), (vii) Type 2A VWD (×1). Laboratories were asked to perform all tests available to them in order to establish a laboratory diagnosis of VWD, and then to comment on the possibility or otherwise of VWD. Overall findings indicated a wide variation in test practice, in the effectiveness of various test procedures in detecting VWD, and in the ability of various composite test panels to identify type 2 VWD subtypes. Firstly, while all laboratories (n = 25) performed tests for FVIII:C activity, von Willebrand factor ‘antigen’ (VWF:Ag) and a functional VWF assay [using the ristocetin cofactor assay (VWF:RCo; n = 23) and/or the collagen binding assay (VWF:CBA; n = 12)], only three laboratories carried out VWF:Multimer analysis. Secondly, for the three quantitative VWF assays, 10/25 (40%) laboratories performed all three, whereas 15/25 (60%) performed only two [VWF:Ag and VWF:RCo (n = 13); VWF:Ag and VWF:CBA (n = 2)]. Thirdly, a variety of assay methodologies were evident for VWF:Ag [ELISA, electro-immuno diffusion (EID), latex immuno-assay (LIA), and VIDAS assay] and VWF:RCo (platelet agglutination/‘aggregometry’ and a ‘functional VWF:RCo-alternative’ ELISA assay). Between method analysis for the quantitative VWF assays showed that the VWF:RCo yielded the greatest degree of inter-laboratory assay variation, and had the poorest overall performance with respect to sensitivity to low levels of VWF. The VWF:CBA also performed better than the VWF:RCo in terms of ability to detect functional VWF ‘discordance’ (i.e. Type 2 VWD). Within VWF:Ag method analysis showed that the EID assay procedure was associated with the greatest variation in assay